Romania's position in the EU extra-European agrifood trade - Camelia Cavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Since the EU accession, Romania's agrifood trade increased significantly, in both volume and value terms. Although the old free trade agreements, that have been in force for the last 15 years, were discontinued when it joined the Single Market, Romania continued its trade relations with its traditional extra-EU partners, under the new EU rules. The EU is currently the largest player in the world agrifood markets, and the 2004 and 2007 enlargements contributed to the consolidation of that position. The present paper is empirically examining the position and contribution of Romania among the other EU member countries to the extra-EU agrifood trade, in terms of values, quantities and directions of flows. The competitiveness of the Romanian extra-community agrifood is analyzed as well, since it improved significantly for the last three years, shifting the trade balance from negative to positive.
Keywords: 330; agrifood trade; extra-EU trade; competitiveness; trade balance